How engagement with influencer marketing campaigns affect the brand performance: a case of stories on Instagram - Myoung, Aerhy (2021)
Influencer marketing englobes many studies that aim increasing the engagement rate of the viewers with the content created by social media influencers, that could be considered opinion leaders. Content has a great impact on the how people consume the information and how this engagement will translate into performance for the influencer marketing campaign adopted by the company in Instagram stories when the performance metric is the number of clicks and installs. The number of stories created and the fit of the influencer’s category with the endorsed product have proven to be relevant predictors of the performance metrics. Furthermore, the format of the content created also has shown to be an important predictor of the number of clicks, also known as swipe ups, to the campaign. Video formats of content delivered more clicks to the influencer campaign when compared to static stories, such as photos. These findings have implications for better understanding how content creation in Instagram stories impact the engagement of the viewers with the product in user acquisition campaigns.